Cr (VI) Removal from Aqueos Solution by Coagulation – Adsorption Integrated System - Sawali, Fikrah Dian Indrawati; Setyawan, Fery; Afandy, Moh Azhar; Mustikaningrum, Mega (Indonesian Journal of Chemical Science, 2024)
Industrial wastewater generated by nickel mining has a high content of heavy metals, one of which is Chromium Hexavalent or Cr(VI) metal. Commonly used methods in reducing Cr(VI) metal concentration are coagulation and adsorption. This method is the most economical, simple and highly efficient method. This research uses the coagulation - adsorption integration system method, which is a combination of coagulation and adsorption methods in stages and uses the same wastewater. The purpose of this research is to see the performance of alum, FeSO4 and a combination of alum: FeSO4 as coagulant and fly ash as adsorbent in the removal of Cr(VI) levels in wastewater samples. Also, the efficiency of using the coagulation - adsorption integration system in the removal of heavy metal levels. The adsorption capacity value of this process can also be calculated. The resulting data were then evaluated using a spectrophotometer visible to assess the reduction of Cr(VI) concentration in wastewater. Based on the experiment, alum type coagulant with a waste and coagulant composition ratio of 2:3 and a stirring time of 60 minutes can reduce Cr(VI) levels to 14.18 mg/L from 100 mg/L. The addition of the adsorption process using fly ash helped reduce the concentration of heavy metal Cr(VI) to 12.15 mg/L and the highest efficiency value was 87.9%, and the adsorption capacity value was 0.087 mg/gram.